Assessment of mitral valve function in children and young adults with hypertrophic cardiomyopathy using three-dimensional echocardiography. (1st June 2021) - Joseph, Navya; Craft, Mary; Mill, LuAnn; Erickson, Christopher C.; Danford, David A.; Kutty, Shelby; Li, Ling
Abstract: Objective: The objective of this study was to assess papillary muscle (PM) and mitral valve (MV) structure and function in children and young adults with mild and moderate hypertrophic cardiomyopathy (HCM) using real-time three-dimensional echocardiography (3DE) and to correlate them with HCM related adverse outcomes. Methods: Transthoracic research 3DE was performed in HCM patients and controls matched for age and gender. Anterolateral and posteromedial PM mass, apical displacement of anterolateral PM, and left ventricular (LV) mass were measured and indexed to body surface area. The MV annulus and leaflet structure and function were analyzed. Individual PMs were manually planimetered by tracing the endocardial borders on each mid systole frame, taking care to distinguish PMs as distinct from the LV wall. Apical PM displacement was expressed as ratio of the distance between the apex and the base of the anterolateral PM to the entire length of the LV lateral wall (APL index). All 3DE measurements were correlated to adverse outcomes. Results: Forty subjects were studied, including 20 HCM patients (age 18.1 ± 9.6 years, 16 male and 4 female), and 20 controls (18.2 ± 9.6 years, 16 male and 4 female). The indexed LV mass in HCM was 74.8 ± 25.8 g/m 2 compared to 50.8 ± 12.4 g/m 2 in controls ( p = 0.001). The anterolateral, posteromedial and combined PM mass were 3.1 ± 2.2 g/m 2, 1.7 ± 1.2 g/m 2 and 4.9 ± 2.7 g/m 2 in HCM, in contrast to respective measurements of 1.1 ± 0.6 g/m 2, 1.2 ± 0.6 g/m 2 and 2.3 ± 0.8 g/m 2 in controls ( p < 0.001, p = 0.062, and p < 0.001, respectively). The mitral valve annular parameters (annulus circumference, height and area) in HCM were not significantly different from controls. The APL index in HCM was less than in controls (0.44 ± 0.07 vs. 0.55 ± 0.04, p < 0.001). The LV lateral wall length and LV mass correlated with adverse HCM outcomes, while the APL index and PM total mass were not associated with adverse events. Conclusion: It is feasible to evaluate PM muscles and MV annulus geometry in children and young adults with HCM using 3DE. The morphologic and functional changes of anterolateral PM may occur in the absence of MV annulus changes. Prospective validation will be required to determine if LV lateral wall length and LV mass may be used as predictors of adverse events. Highlights: It is feasible to assess papillary muscle and mitral valve structure in hypertrophic cardiomyopathy on 3D echocardiography The ratio of the anterolateral papillary muscle insertion length to the LV lateral wall length is reduced in HCM Anterolateral papillary muscle changes preceded mitral valve annulus changes, while LV mass correlated with outcomes